2019
DOI: 10.1186/s12882-019-1298-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of podocyte damage in the etiology of ischemia-reperfusion acute kidney injury and post-injury fibrosis

Abstract: Background To establish a model of chronic renal fibrosis following acute kidney injury (AKI) in BALB/c mice and to observe the effect of AKI on podocyte injury and chronic fibrosis of the kidney. Additional aims included using the model to explore the role of podocyte injury in AKI and post-injury fibrosis. Methods Fifty BALB/C mice were randomly divided into control group (Ctr), sham group (sham), AKI 20 group (renal ischemia, 20 min reperfusion), AKI 30 group (renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
(29 reference statements)
2
40
1
1
Order By: Relevance
“…Considering the relevance of podocyte injury to progressive proteinuria previously demonstrated in ischemia-reperfusion and glomerulosclerosis animal models ( Hara et al, 2015 ; Chen et al, 2019 ), we also evaluated whether acute crystalline-related glomerular injury contributes to proteinuria. Indeed, we observed significant albuminuria in treated animals in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the relevance of podocyte injury to progressive proteinuria previously demonstrated in ischemia-reperfusion and glomerulosclerosis animal models ( Hara et al, 2015 ; Chen et al, 2019 ), we also evaluated whether acute crystalline-related glomerular injury contributes to proteinuria. Indeed, we observed significant albuminuria in treated animals in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical evidence and experimental models of ischemia-reperfusion have revealed that frequently, the recovery of renal function after AKI is incomplete and accompanied by proteinuria, tubular injury and glomerular filtration rate (GFR) decline, leading to end-stage renal disease (ESRD) ( Hingorani et al, 2009 ; Basile et al, 2012 ). Furthermore, other studies using animal models of ischemia-reperfusion and glomerulosclerosis have identified podocyte injury as an etiological factor of progressive proteinuria and kidney function decline ( Hara et al, 2015 ; Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a key component of the innate immune response, Toll-like receptors (TLRs) serve to recognize pathogen-associated molecular patterns (PAMPs) that are present on pathogens, and initiate the innate immune response by producing inflammatory cytokines (14,15). In particular, previous studies have shown that TLR2 could be activated in mice using LPS stimulation, which contribute to the development of septic AKI by enhancing inflammatory cytokine production via the NF-κB signaling pathway (1419). Histological evaluation has demonstrated that TLR2 overactivation in AKI is mainly identified in podocytes, which may be indicative of the important roles podocytes serve in septic AKI pathogenesis (17).…”
Section: Introductionmentioning
confidence: 99%
“…The tubular epithelia produce TNF-α, IL-1, IL-16, IL-8, TGF-β, MCP-1, RANTES, ROS, and fractalkines (48). TNF-α is also produced by macrophages, lymphocytes, endothelial cells, epithelial cells, Schwann cells, mesangial cells, and podocytes in kidney (49). TNF-α is capable of inducing apoptosis and inflammation in renal epithelial cell (16) and can stimulate the production of reactive oxygen species (50).…”
Section: Role Of Cytokines In Pain Regulation During Akimentioning
confidence: 99%